2019
DOI: 10.1016/j.hpb.2019.10.020
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of postoperative thoracic epidural analgesia versus intravenous patient controlled analgesia after major HPB surgery

Abstract: Background: The optimal postoperative analgesic regimen for HPB surgery patients remains controversial. The primary objective of this single-center randomized trial was to compare thoracic epidural analgesia (TEA) to intravenous patient controlled analgesia (PCA) for adequacy of pain control over the first 48 hours after surgery. Methods: Using a 2.5:1 randomization strategy, 140 patients undergoing HPB resections were randomized to TEA (N = 106) or PCA (N = 34). Patient-reported pain was measured on a Likert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The previous evidence for the impact of PCA use on LOS postsurgery has been conflicting (Aloia et al 2019, Dias et al 2016). Our study demonstrated prolongation of LOS (IRR = 1.4) in patients who received PCA during the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous evidence for the impact of PCA use on LOS postsurgery has been conflicting (Aloia et al 2019, Dias et al 2016). Our study demonstrated prolongation of LOS (IRR = 1.4) in patients who received PCA during the immediate postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…A study which followed patients post spinal and orthopaedic surgery did not demonstrate a significant difference in LOS related to PCA compared with conventional analgesics (Dias et al 2016). No studies have shown a clear benefit of PCA in reducing LOS after a surgical procedure (Aloia et al 2019).…”
Section: Introductionmentioning
confidence: 99%